Efektifitas Ibadah Online pada Masa Pandemik di Jemaat GMIT Nazareth Oesapa Timur - Mefibosed Radjah Pono (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2021)
Humans are creatures of worship. Worship is a very important part of human life. In Christianity, worship means the revelation of God in Jesus Christ to humans and human responses through Jesus Christ to God's work. Human response through words, emotions and actions. Online worship is an alternative for many churches to meet the worship needs. The purpose of this study is to describe the effectiveness of the implementation of online worship in the GMIT Nazareth Oesapa Timur Congregation. The method used in this research is descriptive qualitative. Researchers conducted observations and in-depth interviews. From this research, online worship at the GMIT Nazareth Oesapa Timur Congregation has been carried out well, but the results have not been fully effective to help the members to understand the meaning of worship and worship properly. Online worship cannot fully activate the worship that is carried out in church buildings but it can help members of the congregation to worship. Therefore, the church needs to pay attention to the liturgy of worship and provide a good understanding of online worship.